Influence of Coal Bottom Ash as Fine Aggregate Replacement on the Mechanical Properties of Stone Mastic Asphalt - Syakirah Afiza Mohammed; Suhana Koting; Ali Mohammed Babalghaith; Mohd Hafizan Md. Isa; Faridah Hanim Khairuddin (Applied Sciences, 2025)
Coal bottom ash (CBA) is a waste produced by burning coal that presents possible hazards to human well-being and the environment. Rapid economic expansion has increased the utilisation of CBA, resulting in a crisis concerning the disposal of this waste. By employing waste as a replacement for natural materials, it is possible to achieve sustainable and environmentally friendly construction. This study assesses the effects of utilising CBA waste as a replacement for fine aggregate in stone mastic asphalt (SMA) pavement. Seven asphalt mixture proportions were designed, each of which employed a different percentage of CBA (0%, 10%, 20%, 30%, 50%, 70%, and 100%) as a fine aggregate replacement. The performance tests conducted in this research were the Cantabro durability test, resilient modulus test, dynamic creep test, and moisture susceptibility test. The findings showed an improvement in the durability and resistance to permanent deformation of the SMA mixtures with 30% and 50% CBA replacement, respectively. However, further increases in the CBA content caused a decrease in the durability and resistance to permanent deformation. Meanwhile, the stiffness and tensile strength ratio (TSR) value decrease with the use of CBA replacement at any percentage. However, the TSR value of the SMA mixtures with 50% or less CBA replacement was more than 80%, which meets the minimum requirement set by JKR. In conclusion, incorporating CBA into SMA mixture has a positive effect on certain mechanical properties, particularly its durability and resistance to permanent deformation at optimal replacement levels, highlighting its potential to be used as a sustainable material in asphalt pavement construction.